Budaya Kolaborasi Guru dan Orang Tua di Sekolah: Studi pada Madrasah Ibtidaiyah Ummusshabri Kendari: Penelitian - Nasrudin Gito; Damhuri; Laxmi; La Aso; Salmatian Safiudin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Collaboration between teachers and parents is key to educational success, especially in Madrasah Ibtidaiyah, which plays a vital role in shaping students' character and basic competencies. However, its implementation is not always ideal. This study aims to describe and analyze the strategies of Madrasah Ibtidaiyah Ummusshabri Kendari in fostering such collaboration. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The analysis draws on Radcliffe-Brown’s Structural Functionalism to view collaboration as part of the educational social structure, Foucault’s Post-Structuralism to examine power relations and discourse between teachers and parents, and Freire’s Critical Pedagogy to highlight genuine dialogue, role equality, and critical consciousness. The findings reveal four key strategies: (1) effective communication, (2) active parental involvement, (3) strengthening personal and institutional relationships, and (4) regular evaluation and monitoring.